The Effect of Surface Texture on the Joint Shear Strength of AR500 Steel and AA7075 / M. N. Muhamed...[et al.] - M. N., Muhamed; M. Z., Omar; S., Abdullah; Z., Sajuri; W. F. H., W. Zamri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
AA7075 aluminium alloy brazing joint panels caused by shear loading. The use of steel and aluminium laminated metal composite is increasingly popular since they are well known for lightweight application and stiffness properties and this makes them the material of choice in automotive industry. However, the formation of reaction layer phases has limited the application of this method of joining due to the adverse effect of these phases on the strength of the joint. In this work, AR500 steel and AA7075 aluminium alloy interface joint were fabricated by torch brazing method using Al-Si-Zn base material as its filler metal for different types of surface conditions. The joining was evaluated for shear strength performance. The experimental results showed that the highest shear strength for the panel was recorded at 8010 N. Fractures were mostly seen at the joint interface area. In general, the torch brazing process with different surface joining conditions, had facilitated the joining of these dissimilar metals while improving the mechanical properties of the joint.